1997
DOI: 10.1093/rheumatology/36.3.333
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection as a risk factor for septic arthritis

Abstract: We prospectively studied the demographics, the clinical and diagnostic features, the HIV-1 serostatus and the therapeutic response for all new patients with septic arthritis (SA) admitted to the Department of Internal Medicine of the Centre Hospitalier de Kigali, Rwanda, over a 19 month period. SA was diagnosed in 24 patients (10 male, 14 female), of whom 19 (79%) were HIV-1 seropositive (HIVpos). Gonococcal arthritis was found in four patients, all HIVpos. Non-gonococcal bacterial arthritis was established in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 4 publications
1
34
0
1
Order By: Relevance
“…The knees are the most affected joints, also in HIV negative and HIV positive patients, mainly by S. aureus, witch is the most common microorganism found in septic arthritis irrespective of the patient's immune status [9,10,[12][13][14][15][16]. These observations were similar to what we found in our series.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The knees are the most affected joints, also in HIV negative and HIV positive patients, mainly by S. aureus, witch is the most common microorganism found in septic arthritis irrespective of the patient's immune status [9,10,[12][13][14][15][16]. These observations were similar to what we found in our series.…”
Section: Discussionsupporting
confidence: 89%
“…So, Belzenugui found 21 cases of musculoskeletal infections amongst 1832 HIV positive patients, with frequency of 1.15% [9] and Weinstein described 13 vertebral infections amongst 7338 HIV, with a prevalence of 0.23% [11]. But in Rwanda where the seroprevalence of HIV/ AIDS is estimated at 30% in a study [16], 79% of septic arthritis was found in HIV positive patients. These results lead us to the hypothesis that, the number of septic arthritis could be correlated with the prevalence of retroviral infection.…”
Section: Discussionmentioning
confidence: 95%
“…In human immunodeficiency virus (HIV)-infected patients, S. aureus continues to be the most common isolate (approximately 30%) (178). However, increased numbers of opportunistic pathogens are isolated from this patient subset, including S. pneumoniae, mycobacterial species, and fungal species (149,178).…”
Section: Microbiologymentioning
confidence: 99%
“…Based on the PUBMED search, we identified only 11 reports comprising 15 cases of gonococcal arthritis and HIV infection [3][4][5]10,[13][14][15][16][17][18][19]. The demographic data, clinical features, laboratory findings, and outcome of these patients, together with our two patients, are summarized in Table 1.…”
Section: Literature Reviewmentioning
confidence: 99%